2019
DOI: 10.1155/2019/8930904
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media: Long-Term Effect on Central Auditory Nervous System

Abstract: Objectives. To analyze the central auditory nervous system function through behavioral and electrophysiological tests in children with a history of otitis media and subsequent bilateral tubes placement surgery. Methods. The participants were divided into two groups between eight and 14 years old: control group (CG) consisted of 40 children with no history of otitis media; experimental group (EG) consisted of 50 children with documented history of otitis media and undertook a surgery for bilateral tubes placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
1
22
1
4
Order By: Relevance
“…Maruthy and Mannarukrishnaiah [31], Shaffer [30], Sanfins [33], and Colella-Santos [11] reported similar results, i.e., the presence of LLAEP changes in children with a history of OME. In the studies by Maruthy and Mannarukrishnaiah [32], all components of the LLAEP (P1, N1, P2, and N2) were significantly longer in children with an SOM history.…”
Section: Tone Burstmentioning
confidence: 72%
See 4 more Smart Citations
“…Maruthy and Mannarukrishnaiah [31], Shaffer [30], Sanfins [33], and Colella-Santos [11] reported similar results, i.e., the presence of LLAEP changes in children with a history of OME. In the studies by Maruthy and Mannarukrishnaiah [32], all components of the LLAEP (P1, N1, P2, and N2) were significantly longer in children with an SOM history.…”
Section: Tone Burstmentioning
confidence: 72%
“…In addition, children without hearing loss have more coherent responses in both ears, whereas the group of children with a history of OME has a greater dispersion of latencies in all FFR components ( Figure 5). Colella-Santos et al [11] also reported a decrease in VA slope in girls with OME.…”
Section: Frequency Following Responsementioning
confidence: 84%
See 3 more Smart Citations